WOMEN, SLAVERY AND ILLEGAL WORK IN THE TEXTILE INDUSTRY (CIPEEX, 2025)
This research aims to analyze the scenario of women's slave labor in the textile industry. Through the literature review and the analysis of official data, specific aspects of the exploitation of women's labor in the textile industry were demonstrated. The topic is relevant, considering that this type of slave labor is a form of exploitation very present in several countries. Currently, women are still frequently victims of this form of exploitation, suffering gender discrimination, sexual abuse, and harassment. It was possible to understand that the exploitation of female labor in the specific sector studied is much greater than that of men, so that female workers make up the majority in the scenario of slave labor in companies in the textile sector. This exploitation places women in degrading, humiliating, and unworthy conditions and also deprives them of access to the basic rights provided for in labor legislation. It can be concluded that the State, through the Public Ministry of Labor and assertive Public Policies, has a fundamental role in avoiding and ending the cycle of slavery endured by women in contemporary times.
Keywords: Woman's work; Slavery; Textile industry; Exploration; Unworthy work